Upaya Media Alternatif Konde.co dalam Membangun Wacana Kesetaraan Gender di Indonesia - Adinna Islah Perwita; Ade Tuti Turistiati (Institut Ilmu Sosial dan Manajemen STIAMI, 2025)
Konde.co is an alternative media outlet that focuses on voicing women's issues, particularly gender equality. This research analyzes four articles from Konde.co on the theme of gender equality using a qualitative approach with Robert N. Entman's framing model analysis. The aim of this research is to understand Konde.co's efforts in building the discourse of gender equality in society. The results show that in the Define Problems section, the issues of equality that emerge include sexism, discrimination, and even capitalism. In Diagnose Causes, the article delves into the deeper roots of the problem, which is the patriarchal culture. In Make Moral Judgement, it highlights a firm moral judgment against forms of inequality that occur in public discourse, media, state policies, and traditional customs. Lastly, in the Treatment Recommendation, Konde.co not only reveals the issues but also proposes progressive and concrete solutions.